Low-cost implementations of NTRU for pervasive security - Atici, A.C.; Batina, L.; Junfeng Fan; Verbauwhede, I.; Yalcin, S.B.O. (2008 International Conference on Application-Specific Systems, Architectures and Processors, 2008)
NTRU is a public-key cryptosystem based on the shortest vector problem in a lattice which is an alternative to RSA and ECC. This work presents a compact and low power NTRU design that is suitable for pervasive security applications such as RFIDs and sensor nodes. We have designed two architectures, one is only capable of encryption and the other one performs both encryption and decryption. The strategy for the designs includes clock gating of registers, operand isolation and precomputation. This work is also the first one to present a complete NTRU design with encryption/decryption circuitry. Our encryption-only NTRU design has a gate-count of 2.8 kgates and dynamic power consumption of 1.72 muW. Moreover, encryption-decryption NTRU design consumes about 6 muW dynamic power and consists of 10.5 kgates.